Mucormycosis in COVID-19: A systematic review of cases reported worldwide and in India - Singh, Awadhesh Kumar; Singh, Ritu; Joshi, Shashank R.; Misra, Anoop (Diabetes & metabolic syndrome clinical research & reviews, 2021)
There are increasing case reports of rhino-orbital mucormycosis in people with coronavirus disease 2019 (COVID-19), especially from India. Diabetes mellitus (DM) is an independent risk factor for both severe COVID-19 and mucormycosis. We aim to conduct a systematic review of literature to find out the patient's characteristics having mucormycosis and COVID-19. We searched the electronic database of PubMed and Google Scholar from inception until May 13, 2021 using keywords. We retrieved all the granular details of case reports/series of patients with mucormycosis, and COVID-19 reported world-wide. Subsequently we analyzed the patient characteristics, associated comorbidities, location of mucormycosis, use of steroids and its outcome in people with COVID-19. Overall, 101 cases of mucormycosis in people with COVID-19 have been reported, of which 82 cases were from India and 19 from the rest of the world. Mucormycosis was predominantly seen in males (78.9%), both in people who were active (59.4%) or recovered (40.6%) from COVID-19. Pre-existing diabetes mellitus (DM) was present in 80% of cases, while concomitant diabetic ketoacidosis (DKA) was present in 14.9%. Corticosteroid intake for the treatment of COVID-19 was recorded in 76.3% of cases. Mucormycosis involving nose and sinuses (88.9%) was most common followed by rhino-orbital (56.7%). Mortality was noted in 30.7% of the cases. An unholy trinity of diabetes, rampant use of corticosteroid in a background of COVID-19 appears to increase mucormycosis. All efforts should be made to maintain optimal glucose and only judicious use of corticosteroids in patients with COVID-19. •Increasing cases of rhino-orbital mucormycosis in people with COVID-19 are being recently reported.•So far 101 cases of mucormycosis in patients with COVID-19 have been reported of which 82 cases belong to India.•Diabetes was present in 80% of cases, while corticosteroid treatment was given for COVID-19 in 76.3% cases.